Avnet academic application development to increase HOTS for science teachers in North Sumatra - Apriani Sijabat; Golda Novatrasio Sauduran; Christa Voni Roulina Sinaga (Research and Development in Education (RaDEn), 2025)
The limited availability of digital platforms specifically designed to support the development of science teachers' higher order thinking skills (HOTS) is a major problem. This study aims to develop a web-based academic application called Academic Virtual Network (AVNET), designed to enhance HOTS among science teachers in North Sumatra. The study is motivated by the limited availability of digital platforms that specifically support HOTS oriented professional development for science teachers. The research employed the ADDIE development model. Data were collected through needs assessments and expert validation, as well as limited and extensive trials. Expert validation involved specialists in educational technology, instructional design, and science education. The limited trial included 40 science teachers from several districts in North Sumatra. The results show that the Avnet application is highly valid in terms of content, pedagogy, and technical quality, and it is effective in improving teachers’ HOTS, with a gain score of 0.62. These findings indicate that AVNET holds strong potential as a digital solution for HOTS-based teacher professional development, and it is recommended that future studies expand its implementation nationally and integrate it with broader digital learning ecosystems to maximize its impact.